Eco-philosophy and the Perspective of Ecological Conservatism - Niedek, Mikołaj (Studia Ecologiae et Bioethicae, 2021)
This article presents eco-philosophical approaches and ideas presented by Henryk Skolimowski, Roger Scruton, and Pope Francis, in their views on environmental issues. This applies both to the diagnosed causes of the contemporary ecological crisis and constructive proposals to counteract this crisis, by changing our way of thinking and attitudes towards the world. The article begins with an outline of the beginnings of ecological philosophy as a worldview reflection on the relationship of man to the environment. The author’s attention is focused on the ideological profile of eco-philosophical concepts, which determines the progressive or conservative profile of a given eco-philosophy. In the author’s opinion, the green philosophy of R. Scruton, as well as the concept of integral ecology by Pope Francis, can both be classified as ecological conservatism. The eco-philosophy of H. Skolimowski, on the other hand, makes it possible to mediate both progressive and conservative eco-philosophical proposals. According to the author, it is important to be aware of both the differences and the similarities of various eco-philosophies. The common element of the concepts, analysed in the article, is the importance of an ecological, environmentally friendly lifestyle for counteracting the ecological crisis.